2014
DOI: 10.1016/j.drugalcdep.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A randomized pilot clinical trial to evaluate the efficacy of Community Reinforcement and Family Training for Treatment Retention (CRAFT-T) for improving outcomes for patients completing opioid detoxification

Abstract: Background Detoxification with psychosocial counseling remains a standard opioid-use disorder treatment practice but is associated with poor outcomes. This study tested the efficacy of a newly-developed psychosocial intervention, Community Reinforcement Approach and Family Training for Treatment Retention (CRAFT-T), relative to psychosocial treatment as usual (TAU), for improving treatment outcomes. Methods A randomized, 14-week trial with follow-up visits at 6 and 9 months post-randomization conducted at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 19 publications
(21 reference statements)
3
37
0
Order By: Relevance
“…Results from the current study are promising for SO interventions insofar as the majority of patients were able to name an SO who was not using opioids, and described their SO as being supportive of and willing to participate in recovery efforts. Most SOs were immediate family members or partners, suggesting emotionally close relationships, and validating reliance on partners and family members as the designated SO’s in previous interventions (Ino & Hayasida 2000; O’Farrell et al 2008; O’Farrell et al 2008; Brigham et al 2014). Most patients described regular and frequent contact with SO’s, indicating that both the emotional and logistical support of SO’s was accessible for many patients.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Results from the current study are promising for SO interventions insofar as the majority of patients were able to name an SO who was not using opioids, and described their SO as being supportive of and willing to participate in recovery efforts. Most SOs were immediate family members or partners, suggesting emotionally close relationships, and validating reliance on partners and family members as the designated SO’s in previous interventions (Ino & Hayasida 2000; O’Farrell et al 2008; O’Farrell et al 2008; Brigham et al 2014). Most patients described regular and frequent contact with SO’s, indicating that both the emotional and logistical support of SO’s was accessible for many patients.…”
Section: Discussionmentioning
confidence: 78%
“…The only previous study of SO interventions targeting aftercare among opioid users examined an intensive family treatment called Community Reinforcement and Family Training (CRAFT; (Brigham et al 2014). CRAFT works with SOs (defined in this study as relatives or partners that live with or plan to live with the identified patient after randomization) to encourage treatment-resistant individuals with substance use disorders to engage in aftercare (Meyers, Smith & Miller 1998; Kirby et al 1999; Miller, Meyers & Tonigan 1999; Meyers, Smith & Lash 2003; Meyers, Roozen & Smith 2011; Brigham et al 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Brigham et al (2014) was a pilot study in the context of detoxification and the Marsch et al (2014) study in methadone treatment found that replacing some in-person counseling sessions with computerized counseling was superior to standard methadone and hence did not provide evidence that addin g psychosocial treatment improves outcomes. Finally, the study by Ruetsch et al (2012) had only a 66% follow-up rate at 12 months and no urine testing data.…”
mentioning
confidence: 99%